Heteroatom-doped carbon fiber material containing sodium-philic active metal, preparation method of heteroatom-doped carbon fiber material, negative pole piece, sodium ion battery and electric equipment

By doping sodium-philic active metals and heteroatoms in carbon fiber materials, the problems of sodium dendrite growth, limited sodium storage capacity and low cycle life in sodium ion batteries are solved, and higher energy density and better cycle performance are achieved and security.

CN119491309APending Publication Date: 2025-02-21深圳为方能源科技有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411768244.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing sodium ion battery technology has problems such as sodium dendrite growth, limited sodium storage capacity, low cycle life and safety, making it difficult to effectively improve energy density and cycle performance.

Method used

Using carbon fiber materials containing sodium-philic active metals and heteroatom doped, the sodium-philic and electronic structure of the material is improved through nitrogen doping modification and the composite of sodium-philic active metal particles, and the adsorption capacity and cyclic stability of sodium ions are enhanced. .

Benefits of technology

Effectively reduce the nucleation barrier of sodium ions, reduce internal polarization, promote uniform deposition of sodium ions, improve the safety and electrochemical performance of the battery, and extend the cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119491309A_ABST
    Figure CN119491309A_ABST
Patent Text Reader

Abstract

The invention provides a heteroatom-doped carbon fiber material containing sodium-philic active metal, a preparation method of the heteroatom-doped carbon fiber material, a negative pole piece, a sodium ion battery and electric equipment, and relates to the field of sodium ion batteries. The heteroatom-doped carbon fiber material containing the sodium-philic active metal comprises nitrogen-doped modified carbon fibers and sodium-philic active metal particles compounded on the inner walls of the doped modified carbon fibers, the metal elements of the sodium-philic active metal particles comprise at least one of Cu, Mg, Al, Zn, Ga, Ge, Sr, Zr, Nb, Mo, Ag, In, Sn, Sb, Te and Pb. According to the heteroatom-doped carbon fiber material containing the sodium-philic active metal, by optimizing the structure and composition of the material, the problems of volume expansion, electrode smashing and the like in the circulation process can be reduced, so that the cycle life of the material is prolonged, and the stability of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of sodium ion batteries, and in particular to a carbon fiber material containing a sodium-philic active metal and doped with heteroatoms, a preparation method thereof, a negative electrode sheet, a sodium ion battery and electrical equipment. Background Art

[0002] There are still some problems with existing sodium-ion batteries and negative electrode technologies. Using ultra-thin metallic sodium as the negative electrode material can significantly improve the energy density of sodium-ion batteries, but the flexibility and viscosity of metallic sodium itself make it very difficult to produce ultra-thin sodium foil. At the same time, sodium metal has problems such as dendrite growth, unlimited volume expansion, and low Coulomb efficiency, which may cause internal short circuits or performance degradation in the battery, thereby reducing the battery's cycle life and safety. Commercial hard carbon materials have problems such as low capacity and gas generation in sodium-ion batteries, which limits the widespread application of sodium-ion batteries. In order to improve the energy density, directly using pure aluminum foil or copper foil current collectors as sodium-free negative electrodes and combining them with highly active deposited sodium metal will cause side reactions between the negative electrode and the electrolyte, resulting in extremely poor cycle performance. However, the existing sodium ion battery technology still has the following problems: on the one hand, the carbon element in the composite negative electrode is not a good sodium-loving element, and sodium ions are difficult to deposit evenly, which easily produces sodium dendrites, causing battery safety problems; on the other hand, sodium ions are mostly deposited on the surface of the carbon negative electrode, with limited sodium storage capacity and no obvious capacity improvement; at the same time, the deposited sodium metal is easily corroded by the electrolyte and undergoes side reactions, and cannot form a stable SEI layer, resulting in a low cycle life. Therefore, how to avoid these problems and obtain a sodium ion battery with strong sodium storage capacity and large capacity has become a technical problem that needs to be solved urgently. Summary of the invention

[0003] The purpose of this application is to provide a carbon fiber material containing sodium-philic active metals and doped with heteroatoms, and a preparation method thereof, a negative electrode sheet, a sodium ion battery and electrical equipment to solve the above-mentioned problems.

[0004] To achieve the above objectives, this application adopts the following technical solutions:

[0005] The present application provides a carbon fiber material containing sodium-philic active metal and doped with heteroatoms, including nitrogen-doped modified carbon fiber and sodium-philic active metal particles composited on the inner wall of the doped modified carbon fiber;

[0006] The metal element of the sodium-philic active metal particles includes at least one of Cu, Mg, Al, Zn, Ga, Ge, Sr, Zr, Nb, Mo, Ag, In, Sn, Sb, Te, and Pb.

[0007] Optionally, the nitrogen-doped modified carbon fiber includes at least one of nitrogen-doped modified graphitized carbon and amorphous carbon.

[0008] Optionally, the nitrogen content in the nitrogen-doped modified carbon fiber is 5-10 wt %.

[0009] Optionally, the sodium-philic active metal particles are nanoparticles, and the particle size of the nanoparticles is 0.1-100 nm.

[0010] Optionally, the content of the sodium-philic active metal particles is 3-10 wt %.

[0011] The present application also provides a method for preparing a carbon fiber material containing a sodium-philic active metal and doped with a heteroatom, the method comprising:

[0012] Mixing raw materials including a sodium-philic active metal salt, an organic reducing agent, a nitrogen-containing organic solvent, and a nitrogen-containing carbon precursor to obtain a mixed solution;

[0013] Spinning the mixed solution to obtain a carbon fiber precursor;

[0014] The carbon fiber precursor is carbonized and cooled to obtain the carbon fiber containing sodium-philic active metal and doped with heteroatoms.

[0015] Optionally, the sodium-philic active metal salt comprises a sodium-philic active metal halide and / or a sodium-philic active metal nitrate. Preferably, the sodium-philic active metal salt comprises antimony chloride or silver nitrate.

[0016] Optionally, the organic reducing agent includes at least one of formaldehyde, acetaldehyde, propionaldehyde, glucose, and polymethyl methacrylate.

[0017] Optionally, the nitrogen-containing organic solvent includes at least one of N,N-dimethylformamide, N-methylcarbamates, N,N′-dimethylcarbamates, phenylcarbamates and thiocarbamates.

[0018] Optionally, the nitrogen-containing carbon precursor includes at least one of dopamine, melamine, and polypyridine.

[0019] Optionally, the sodium-philic active metal salt includes antimony chloride, copper chloride, magnesium chloride, aluminum chloride, zinc chloride, gallium chloride, germanium chloride, strontium chloride, zirconium chloride, niobium chloride, molybdenum chloride, silver chloride, indium chloride, tin chloride, antimony chloride, tellurium chloride, lead chloride; at least one of silver nitrate, copper nitrate, magnesium nitrate, aluminum nitrate, zinc nitrate, gallium nitrate, germanium nitrate, strontium nitrate, zirconium nitrate, niobium nitrate, molybdenum nitrate, indium nitrate, tin nitrate, antimony nitrate, tellurium nitrate, and lead nitrate.

[0020] Optionally, the mass molar ratio of the sodium-philic active metal salt, the organic reducing agent, the nitrogen-containing organic solvent, and the nitrogen-containing carbon precursor is 1-10:1-10:1-10:1-10.

[0021] Optionally, the stirring temperature is set to 50-80° C. and the stirring time is set to 6-12 hours when the raw materials are mixed.

[0022] Optionally, the spinning is continuous electrospinning, during which the rotation voltage is 10-20 kV, the receiving distance is 10-20 cm, the pushing speed is 1-10 μL / min, the rotation speed is 200-500 rpm / min, the humidity is 20-60%, and the temperature is 30-60°C.

[0023] Optionally, the carbonization of the carbon fiber precursor is carried out in an inert gas atmosphere, and the inert gas includes argon or nitrogen.

[0024] Optionally, during the carbonization process of the carbon fiber precursor, the heating rate is 2-10°C / min, the heating temperature is 500-1000°C, and the heating time is 2-6h.

[0025] The present application also provides a sodium ion battery negative electrode plate, the raw materials of which include a negative electrode current collector and a negative electrode active layer, the raw materials of the negative electrode active layer are carbon fiber materials containing sodium-philic active metals and doped with heteroatoms, and the raw materials of the negative electrode active layer also include a binder and conductive carbon.

[0026] Optionally, based on the mass of the negative electrode active layer itself being 100%, the mass ratio of the carbon fiber containing the sodium-philic active metal and doped with heteroatoms, the binder, and the conductive carbon is 80-90%: 5-10%: 5-10%.

[0027] Optionally, the binder includes at least one of styrene-butadiene rubber and polyvinylidene fluoride.

[0028] Optionally, the conductive carbon includes one of acetylene black, conductive carbon fiber, and graphene.

[0029] Optionally, the current collector includes aluminum foil and / or copper foil.

[0030] Optionally, the current collector has a thickness of 10-20 μm.

[0031] Optionally, the thickness of the negative electrode active layer is 5-50 μm.

[0032] The present application also provides a sodium ion battery, comprising the sodium ion battery negative electrode plate.

[0033] The present application also provides an electrical device, including the sodium ion battery.

[0034] Compared with the prior art, the beneficial effects of this application include:

[0035] The carbon fiber material containing sodium-philic active metal and heteroatom doping provided by the present application, on the one hand, can effectively reduce the sodium ion nucleation barrier, reduce internal polarization, promote the uniform deposition of sodium ions, effectively avoid the growth of sodium dendrites, and improve the safety performance of the battery by using the sodium-philic active element as the sodium-philic nucleation site; on the other hand, the metal single atom doping can adjust the electronic structure of the carbon fiber material to produce new active centers and reaction pathways. These new active centers and reaction pathways help to guide the uniform deposition and stripping of sodium ions, further improving the electrochemical performance of the battery. In addition, the doping of heteroatoms can further increase the electrochemical active sites of the carbon fiber material, which can more effectively adsorb sodium ions; the rapid transmission of electrons can be achieved by heteroatom doping, which improves the rate performance and cycle life of the battery, and the volume expansion of the deposited sodium metal is limited by porous carbon, which improves the safety performance and cycle life of the battery. In addition, the combination of sodium-philic active metals and carbon fibers and the doping of heteroatoms can work together on the cyclic stability of the material. By optimizing the structure and composition of the material, the volume expansion and electrode crushing problems during the cycle can be reduced, thereby improving the cycle life and stability of the material.

[0036] The preparation method of the carbon fiber material containing sodium-philic active metal and doped with heteroatoms provided in the present application is simple in process, easy to industrialize and has broad application prospects.

[0037] The negative electrode plate provided in the present application uses the above-mentioned carbon fiber material containing sodium-philic active metal and doped with heteroatoms as raw material, which can effectively improve the safety performance, cycle performance and stability of the battery.

[0038] The sodium ion battery and electrical equipment provided in this application have excellent electrical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0040] Figure 1 Schematic diagram of sodium deintercalation of the negative electrode sheet prepared in Example 1.

[0041] Figure 2 This is a SEM image of the carbon fiber material containing sodium-philic active metal and doped with heteroatoms prepared in Example 1.

[0042] Figure 3 This is the XRD pattern of the nitrogen atom-doped carbon fiber material prepared in Comparative Example 1. DETAILED DESCRIPTION

[0043] As used herein:

[0044] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0045] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0046] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0047] In these examples, parts and percentages are by mass unless otherwise indicated.

[0048] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0049] “And / or” is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0050] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows:

[0051] In a first aspect, the present application provides a carbon fiber material containing sodium-philic active metal and doped with heteroatoms, including nitrogen-doped modified carbon fiber and sodium-philic active metal particles composited on the inner wall of the doped modified carbon fiber;

[0052] The metal element of the sodium-philic active metal particles includes at least one of Cu, Mg, Al, Zn, Ga, Ge, Sr, Zr, Nb, Mo, Ag, In, Sn, Sb, Te, and Pb.

[0053] Carbon fiber materials containing sodium-philic active metals and doped with heteroatoms can significantly improve the sodium affinity of the material, enhance the adsorption capacity of sodium ions, improve the electronic structure of the material, and improve the cyclic stability of the material through the sodium-philic active metal ions.

[0054] In an optional embodiment, the nitrogen-doped modified carbon fiber includes at least one of nitrogen-doped modified graphitized carbon and amorphous carbon.

[0055] In an optional embodiment, the nitrogen content in the nitrogen-doped modified carbon fiber is 5-10 wt %.

[0056] Nitrogen atoms contain lone pairs of electrons, which can improve the conductivity of carbon materials and their wettability in electrolytes after doping. This helps to reduce the contact resistance between carbon fiber materials and electrolytes, thereby improving electrochemical performance. Excessive nitrogen doping may lead to a decrease in the structural stability of carbon fiber materials, thereby affecting their cycle performance and service life. By controlling the amount of nitrogen doping, it can be ensured that carbon fiber materials maintain good structural stability and cycle performance while maintaining high electrochemical properties.

[0057] Optionally, the nitrogen content in the nitrogen-doped modified carbon fiber may be 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, or any value between 5-10wt%.

[0058] In an optional embodiment, the sodium-philic active metal particles are nanoparticles, and the particle size of the nanoparticles is 0.1-100 nm.

[0059] Optionally, the particle size of the nanoparticles can be 0.1nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, or any value between 0.1-100nm.

[0060] In an optional embodiment, the content of the sodium-philic active metal particles is 3-10 wt %.

[0061] Optionally, the content of the sodium-philic active metal particles can be 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, or any value between 3-10wt%.

[0062] In a second aspect, the present application also provides a method for preparing a carbon fiber material containing a sodium-philic active metal and doped with a heteroatom, the method comprising:

[0063] Mixing raw materials including a sodium-philic active metal salt, an organic reducing agent, a nitrogen-containing organic solvent, and a nitrogen-containing carbon precursor to obtain a mixed solution;

[0064] Spinning the mixed solution to obtain a carbon fiber precursor;

[0065] The carbon fiber precursor is carbonized and cooled to obtain the carbon fiber containing sodium-philic active metal and doped with heteroatoms.

[0066] In an optional embodiment, the sodium-philic active metal salt includes a sodium-philic active metal halide and / or a sodium-philic active metal nitrate. Preferably, the sodium-philic active metal salt includes antimony trichloride and silver nitrate.

[0067] In an optional embodiment, the organic reducing agent includes at least one of formaldehyde, acetaldehyde, propionaldehyde, glucose, and polymethyl methacrylate.

[0068] In an optional embodiment, the nitrogen-containing organic solvent includes at least one of N,N-dimethylformamide, N-methylcarbamates, N,N′-dimethylcarbamates, phenylcarbamates and thiocarbamates.

[0069] In an optional embodiment, the nitrogen-containing carbon precursor includes at least one of dopamine, melamine, and polypyridine.

[0070] In an optional embodiment, the sodium-philic active metal salt includes antimony chloride, copper chloride, magnesium chloride, aluminum chloride, zinc chloride, gallium chloride, germanium chloride, strontium chloride, zirconium chloride, niobium chloride, molybdenum chloride, silver chloride, indium chloride, tin chloride, antimony chloride, tellurium chloride, lead chloride; at least one of silver nitrate, copper nitrate, magnesium nitrate, aluminum nitrate, zinc nitrate, gallium nitrate, germanium nitrate, strontium nitrate, zirconium nitrate, niobium nitrate, molybdenum nitrate, indium nitrate, tin nitrate, antimony nitrate, tellurium nitrate, and lead nitrate.

[0071] In an optional embodiment, the mass molar ratio of the sodium-philic active metal salt, the organic reducing agent, the nitrogen-containing organic solvent, and the nitrogen-containing carbon precursor is 1-10:1-10:1-10:1-10.

[0072] In an optional embodiment, the stirring temperature is set to 50-80° C. and the stirring time is set to 6-12 hours when the raw materials are mixed.

[0073] Optionally, the stirring temperature set when the raw materials are mixed can be 50° C., 55° C., 60° C., 65° C., 70° C., 75° C., 80° C., or any value between 50-80° C. The stirring time can be 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, or any value between 6-12 h.

[0074] In an optional embodiment, the spinning is continuous electrospinning. During the continuous electrospinning process, the rotation voltage is 10-20 kV, the receiving distance is 10-20 cm, the push speed is 1-10 μL / min, the rotation speed is 200-500 rpm / min, the humidity is 20-60%, and the temperature is 30-60°C.

[0075] Optionally, the rotation voltage can be 10kV, 11kV, 12kV, 13kV, 14kV, 15kV, 16kV, 17kV, 18kV, 19kV, 20kV, or any value between 10-20kV. Optionally, the receiving distance can be 10cm, 11cm, 12cm, 13cm, 14cm, 15cm, 16cm, 17cm, 18cm, 19cm, 20cm, or any value between 10-20cm. Optionally, the push speed can be 1μL / min, 2μL / min, 3μL / min, 4μL / min, 5μL / min, 6μL / min, 7μL / min, 8μL / min, 9μL / min, 10μL / min, or any value between 1-10μL / min. Optionally, the rotation speed can be 200rpm / min, 250rpm / min, 300rpm / min, 350rpm / min, 400rpm / min, 450rpm / min, 500rpm / min, or any value between 200-500rpm / min. Optionally, the humidity can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, or any value between 20-60%. Optionally, the temperature can be 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, or any value between 30-60°C.

[0076] In an optional embodiment, the carbonization process of the carbon fiber precursor is carried out in an inert gas atmosphere, and the inert gas includes argon or nitrogen.

[0077] In an optional embodiment, during the carbonization process of the carbon fiber precursor, the heating rate is 2-10° C. / min, the heating temperature is 500-1000° C., and the heating time is 2-6 h.

[0078] Optionally, the heating rate may be 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, or any value between 2-10°C / min. Optionally, the heating temperature may be 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, or any value between 500-1000°C. Optionally, the heating time may be 2h, 3h, 4h, 5h, 6h, or any value between 2-6h.

[0079] In a third aspect, the present application also provides a sodium ion battery negative electrode plate, the raw materials of which include a negative electrode current collector and a negative electrode active layer, the raw materials of the negative electrode active layer include a carbon fiber material containing a sodium-philic active metal and doped with heteroatoms, and the raw materials of the negative electrode active layer also include a binder and conductive carbon.

[0080] In an optional embodiment, based on the mass of the negative electrode active layer itself being 100%, the mass ratio of the carbon fiber containing sodium-philic active metal and doped with heteroatoms, the binder, and the conductive carbon is 80-90%: 5-10%: 5-10%.

[0081] Optionally, the mass ratio of the carbon fiber containing sodium-philic active metal and doped with heteroatoms, the binder, and the conductive carbon can be 80%:10%:10%, 90%:5%:5%, 85%:8%:7%, 88%:6%:6%, or any range of 80-90%:5-10%:5-10%, based on the mass of the negative electrode active layer itself as 100%.

[0082] In an optional embodiment, the binder includes at least one of styrene-butadiene rubber and polyvinylidene fluoride.

[0083] In an optional embodiment, the conductive carbon includes one of acetylene black, conductive carbon fiber, and graphene.

[0084] In an optional embodiment, the current collector includes aluminum foil and / or copper foil.

[0085] In an optional embodiment, the thickness of the current collector is 10-20 μm.

[0086] Optionally, the thickness of the current collector may be 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, or any value between 10-20 μm.

[0087] In an optional embodiment, the thickness of the negative electrode active layer is 5-50 μm.

[0088] Optionally, the thickness of the negative electrode active layer may be 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, or any value between 5 and 50 μm.

[0089] In a fourth aspect, the present application also provides a sodium ion battery, comprising the sodium ion battery negative electrode plate.

[0090] In a fifth aspect, the present application also provides an electrical device, including the sodium ion battery, such as electric cars, electric bicycles, smart phones, tablet computers, smart watches, health detectors, drones, etc.

[0091] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0092] Example 1

[0093] This embodiment provides a carbon fiber material containing sodium-philic active metal and doped with heteroatoms, and the specific preparation process is as follows:

[0094] Antimony trichloride, polymethyl methacrylate, N,N-dimethylformamide and melamine were mixed in a mass molar ratio of 2:1:8:8, and stirred continuously at 60°C for 8 hours to completely dissolve the mixed solution into a colorless and transparent high-viscosity solution.

[0095] The above solution was loaded into a disposable syringe, and the metal needle was fixed on the electrospinning device. After continuous electrospinning, the entire electrospinning membrane was peeled off and heated in a vacuum oven. The electrospinning device was set to work with a rotation voltage of 15kV, a receiving distance of 15cm, a push speed of 1-10μL / min, a rotation speed of 300rpm / min, a humidity of 40%, and a temperature of 45°C. The heating temperature in the vacuum oven was 120°C for 8h.

[0096] The prepared precursor film is placed in a tubular furnace for carbonization, the atmosphere is argon, the heating rate is 2°C / min, the heating temperature is 800°C, the heating time is 4h, and after cooling to room temperature, carbon fibers containing sodium-philic active metals and doped with heteroatoms are obtained. The prepared carbon fibers containing sodium-philic active metals and doped with heteroatoms are amorphous carbon with a nitrogen content of 5%, a sodium-philic active metal content of 5%, and a sodium-philic metal particle particle size range of 20-100nm. The SEM image of the prepared carbon fiber material containing sodium-philic active metals and doped with heteroatoms is shown below: Figure 2 shown.

[0097] This embodiment also provides a sodium ion battery negative electrode plate, and the preparation method thereof is as follows:

[0098] The carbon fiber, acetylene black, and polyvinylidene fluoride prepared above containing sodium-philic active metal and doped with heteroatoms are weighed and mixed in a mass ratio of 80%:10%:10%, and N-methylpyrrolidone is added with a solid content ratio of 30%, and a mixed slurry is prepared by high-speed ball milling. The mixed slurry is coated on an aluminum foil current collector by a coating machine, vacuum dried, and rolled to obtain a negative electrode sheet for a sodium ion battery. Among them, the thickness of the aluminum foil current collector is 10 μm, and the thickness of the negative electrode active layer is 20 μm.

[0099] This embodiment also provides a sodium ion battery, and the preparation method thereof is as follows:

[0100] The negative electrode sheet uses the above-mentioned sodium ion battery negative electrode sheet, the positive electrode sheet uses O3 layered oxide, and the electrolyte uses commercial sodium battery electrolyte (manufacturer is Dongguan Kelude Experimental Equipment Technology Co., Ltd., product batch number is 20240812). The remaining steps are assembled into a 2032 button-type sodium full battery according to conventional methods. Schematic diagram of sodium deintercalation of the negative electrode sheet (inhibiting the growth of sodium dendrites) as shown in the figure. Figure 1 shown.

[0101] Example 2

[0102] This embodiment provides a carbon fiber material containing sodium-philic active metal and doped with heteroatoms, and the specific preparation process is as follows:

[0103] Antimony trichloride, polymethyl methacrylate, N,N-dimethylformamide and melamine were mixed in a mass molar ratio of 2:1:8:8, and stirred continuously at 60°C for 8 hours to completely dissolve the mixed solution into a colorless and transparent high-viscosity solution.

[0104] The above solution was loaded into a disposable syringe, and the metal needle was fixed on the electrospinning device. After continuous electrospinning, the entire electrospinning membrane was peeled off and heated in a vacuum oven. The electrospinning device was set to work with a rotation voltage of 15kV, a receiving distance of 15cm, a push speed of 1-10μL / min, a rotation speed of 300rpm / min, a humidity of 40%, and a temperature of 45°C. The heating temperature in the vacuum oven was 120°C for 8h.

[0105] The prepared precursor film is placed in a tubular furnace for carbonization, the atmosphere is argon, the heating rate is 2°C / min, the heating temperature is 800°C, the heating time is 4h, and after cooling to room temperature, a carbon fiber containing a sodium-philic active metal and doped with heteroatoms is obtained. The prepared carbon fiber containing a sodium-philic active metal and doped with heteroatoms is amorphous carbon, with a nitrogen content of 5%, a sodium-philic active metal content of 5%, and a particle size range of 20-100nm for the sodium-philic metal particles.

[0106] This embodiment also provides a sodium ion battery negative electrode plate, and the preparation method thereof is as follows:

[0107] The carbon fiber, acetylene black, and polyvinylidene fluoride prepared above containing sodium-philic active metal and doped with heteroatoms are weighed and mixed in a mass ratio of 90%:5%:5%, and N-methylpyrrolidone is added with a solid content ratio of 35%, and a mixed slurry is prepared by high-speed ball milling. The mixed slurry is coated on an aluminum foil current collector by a coating machine, vacuum dried, and then rolled to obtain a negative electrode sheet for a sodium ion battery. The thickness of the aluminum foil current collector is 10 μm, and the thickness of the negative electrode active layer is 20 μm.

[0108] This embodiment also provides a sodium ion battery, and the preparation method thereof is as follows:

[0109] The negative electrode sheet uses the above-mentioned sodium ion battery negative electrode sheet, the positive electrode sheet uses O3 layered oxide, the electrolyte uses commercial sodium battery electrolyte (manufacturer is Dongguan Kelude Experimental Equipment Technology Co., Ltd., product batch number is 20240812), and the remaining steps are assembled into a 2032 button-type sodium full battery according to conventional methods.

[0110] Example 3

[0111] This embodiment provides a carbon fiber material containing sodium-philic active metal and doped with heteroatoms, and the specific preparation process is as follows:

[0112] Antimony trichloride, polymethyl methacrylate, N,N-dimethylformamide and melamine were mixed in a mass molar ratio of 2:1:8:8, and stirred continuously at 60°C for 8 hours to completely dissolve the mixed solution into a colorless and transparent high-viscosity solution.

[0113] The above solution was loaded into a disposable syringe, and the metal needle was fixed on the electrospinning device. After continuous electrospinning, the entire electrospinning membrane was peeled off and heated in a vacuum oven. The electrospinning device was set to work with a rotation voltage of 15kV, a receiving distance of 15cm, a push speed of 1-10μL / min, a rotation speed of 300rpm / min, a humidity of 40%, and a temperature of 45°C. The heating temperature in the vacuum oven was 120°C for 8h.

[0114] The prepared precursor film is placed in a tubular furnace for carbonization, the atmosphere is argon, the heating rate is 2°C / min, the heating temperature is 800°C, the heating time is 4h, and after cooling to room temperature, a carbon fiber containing a sodium-philic active metal and doped with heteroatoms is obtained. The prepared carbon fiber containing a sodium-philic active metal and doped with heteroatoms is amorphous carbon, with a nitrogen content of 5%, a sodium-philic active metal content of 5%, and a particle size range of 20-100nm for the sodium-philic metal particles.

[0115] This embodiment also provides a sodium ion battery negative electrode plate, and the preparation method thereof is as follows:

[0116] The carbon fiber, acetylene black, and polyvinylidene fluoride prepared above containing sodium-philic active metal and heteroatom doped are weighed and mixed evenly in a mass ratio of 90%:5%:5%, and N-methylpyrrolidone is added with a solid content ratio of 40%, and a mixed slurry is prepared by high-speed ball milling. The mixed slurry is coated on an aluminum foil current collector by a coating machine, vacuum dried, and rolled to obtain a negative electrode sheet for a sodium ion battery. The thickness of the aluminum foil current collector is 10 μm, and the thickness of the negative electrode active layer is 50 μm.

[0117] This embodiment also provides a sodium ion battery, and the preparation method thereof is as follows:

[0118] The negative electrode sheet uses the above-mentioned sodium ion battery negative electrode sheet, the positive electrode sheet uses P2 layered oxide, the electrolyte uses commercial sodium battery electrolyte (the manufacturer is Dongguan Kelude Experimental Equipment Technology Co., Ltd., the product batch is 20240812), and the remaining steps are assembled into a 2032 button-type sodium full battery according to conventional methods.

[0119] Example 4

[0120] This embodiment provides a carbon fiber material containing sodium-philic active metal and doped with heteroatoms, and the specific preparation process is as follows:

[0121] Silver nitrate, glucose, N,N-dimethylformamide and melamine were mixed in a mass molar ratio of 2:2:8:8, and stirred continuously at 60°C for 8 hours to completely dissolve the mixed solution into a colorless and transparent high-viscosity solution.

[0122] The above solution was loaded into a disposable syringe, and the metal needle was fixed on the electrospinning device. After continuous electrospinning, the entire electrospinning membrane was peeled off and heated in a vacuum oven. The electrospinning device was set to work with a rotation voltage of 15kV, a receiving distance of 15cm, a push speed of 1-10μL / min, a rotation speed of 300rpm / min, a humidity of 40%, and a temperature of 45°C. The heating temperature in the vacuum oven was 120°C for 8h.

[0123] The prepared precursor film is placed in a tubular furnace for carbonization, the atmosphere is argon, the heating rate is 2°C / min, the heating temperature is 800°C, the heating time is 4h, and after cooling to room temperature, a carbon fiber containing a sodium-philic active metal and doped with heteroatoms is obtained. The prepared carbon fiber containing a sodium-philic active metal and doped with heteroatoms is amorphous carbon, with a nitrogen content of 6%, a sodium-philic active metal content of 4%, and a particle size range of 20-100nm for the sodium-philic metal particles.

[0124] This embodiment also provides a sodium ion battery negative electrode plate, and the preparation method thereof is as follows:

[0125] The carbon fiber, acetylene black, and polyvinylidene fluoride prepared above containing sodium-philic active metal and doped with heteroatoms are weighed and mixed in a mass ratio of 80%:10%:10%, and N-methylpyrrolidone is added with a solid content ratio of 30%, and a mixed slurry is prepared by high-speed ball milling. The mixed slurry is coated on an aluminum foil current collector by a coating machine, vacuum dried, and rolled to obtain a negative electrode sheet for a sodium ion battery. Among them, the thickness of the aluminum foil current collector is 10 μm, and the thickness of the negative electrode active layer is 20 μm.

[0126] This embodiment also provides a sodium ion battery, and the preparation method thereof is as follows:

[0127] The negative electrode sheet uses the above-mentioned sodium ion battery negative electrode sheet, the positive electrode sheet uses O3 layered oxide, the electrolyte uses commercial sodium battery electrolyte (manufacturer is Dongguan Kelude Experimental Equipment Technology Co., Ltd., product batch number is 20240812), and the remaining steps are assembled into a 2032 button-type sodium full battery according to conventional methods.

[0128] Example 5

[0129] This embodiment provides a carbon fiber material containing sodium-philic active metal and doped with heteroatoms, and the specific preparation process is as follows:

[0130] Tin chloride, polymethyl methacrylate, N,N-dimethylformamide and melamine were mixed in a mass molar ratio of 2:1:9:9, and stirred continuously at 60°C for 8 hours to completely dissolve the mixed solution into a colorless and transparent high-viscosity solution.

[0131] The above solution was loaded into a disposable syringe, and the metal needle was fixed on the electrospinning device. After continuous electrospinning, the entire electrospinning membrane was peeled off and heated in a vacuum oven. The electrospinning device was set to work with a rotation voltage of 15kV, a receiving distance of 15cm, a push speed of 1-10μL / min, a rotation speed of 300rpm / min, a humidity of 40%, and a temperature of 45°C. The heating temperature in the vacuum oven was 120°C for 8h.

[0132] The prepared precursor film is placed in a tubular furnace for carbonization, the atmosphere is argon, the heating rate is 2°C / min, the heating temperature is 800°C, the heating time is 4h, and after cooling to room temperature, a carbon fiber containing a sodium-philic active metal and doped with heteroatoms is obtained. The prepared carbon fiber containing a sodium-philic active metal and doped with heteroatoms is amorphous carbon, with a nitrogen content of 8%, a sodium-philic active metal content of 3.5%, and a particle size range of 20-100nm for the sodium-philic metal particles.

[0133] This embodiment also provides a sodium ion battery negative electrode plate, and the preparation method thereof is as follows:

[0134] The carbon fiber, acetylene black, and polyvinylidene fluoride prepared above containing sodium-philic active metal and doped with heteroatoms are weighed and mixed in a mass ratio of 80%:10%:10%, and N-methylpyrrolidone is added with a solid content ratio of 30%, and a mixed slurry is prepared by high-speed ball milling. The mixed slurry is coated on an aluminum foil current collector by a coating machine, vacuum dried, and rolled to obtain a negative electrode sheet for a sodium ion battery. Among them, the thickness of the aluminum foil current collector is 10 μm, and the thickness of the negative electrode active layer is 20 μm.

[0135] This embodiment also provides a sodium ion battery, and the preparation method thereof is as follows:

[0136] The negative electrode sheet uses the above-mentioned sodium ion battery negative electrode sheet, the positive electrode sheet uses O3 layered oxide, the electrolyte uses commercial sodium battery electrolyte (manufacturer is Dongguan Kelude Experimental Equipment Technology Co., Ltd., product batch number is 20240812), and the remaining steps are assembled into a 2032 button-type sodium full battery according to conventional methods.

[0137] Comparative Example 1

[0138] This comparative example provides a carbon fiber material, and the specific preparation process is as follows:

[0139] N,N-dimethylformamide and melamine were mixed in a mass molar ratio of 8:8, and stirred continuously at 60°C for 8 hours to completely dissolve the mixed solution into a colorless and transparent high-viscosity solution.

[0140] The above solution was loaded into a disposable syringe, and the metal needle was fixed on the electrospinning device. After continuous electrospinning, the entire electrospinning membrane was peeled off and heated in a vacuum oven. The electrospinning device was set to work with a rotation voltage of 15kV, a receiving distance of 15cm, a push speed of 1-10μL / min, a rotation speed of 300rpm / min, a humidity of 40%, and a temperature of 45°C. The heating temperature in the vacuum oven was 120°C for 8h. The prepared nitrogen atom-doped carbon fiber is amorphous carbon with a nitrogen content of 8%.

[0141] The prepared precursor film was placed in a tubular furnace for carbonization, the atmosphere was argon, the heating rate was 2℃ / min, the heating temperature was 800℃, the heating time was 4h, and after cooling to room temperature, carbon fibers containing sodium-philic active metals and doped with heteroatoms were obtained. The XRD pattern of the prepared carbon fiber material doped with nitrogen heteroatoms is shown in the figure below: Figure 3 shown.

[0142] This comparative example also provides a sodium ion battery negative electrode sheet, and the preparation method thereof is as follows:

[0143] The carbon fiber, acetylene black, and polyvinylidene fluoride prepared above containing sodium-philic active metal and doped with heteroatoms are weighed and mixed in a mass ratio of 80%:10%:10%, and N-methylpyrrolidone is added with a solid content ratio of 30%, and a mixed slurry is prepared by high-speed ball milling. The mixed slurry is coated on an aluminum foil current collector by a coating machine, vacuum dried, and rolled to obtain a negative electrode sheet for a sodium ion battery. Among them, the thickness of the aluminum foil current collector is 10 μm, and the thickness of the negative electrode active layer is 20 μm.

[0144] This comparative example also provides a sodium ion battery, and its preparation method is as follows:

[0145] The negative electrode sheet uses the above-mentioned sodium ion battery negative electrode sheet, the positive electrode sheet uses O3 layered oxide, the electrolyte uses commercial sodium battery electrolyte (manufacturer is Dongguan Kelude Experimental Equipment Technology Co., Ltd., product batch number is 20240812), and the remaining steps are assembled into a 2032 button-type sodium full battery according to conventional methods.

[0146] Comparative Example 2

[0147] This comparative example provides a carbon fiber material containing a sodium-philic active metal and doped with heteroatoms, and the specific preparation process is as follows:

[0148] Antimony trichloride and polymethyl methacrylate were mixed in a mass molar ratio of 2:1, and stirred continuously at 60°C for 8 hours to completely dissolve the mixed solution into a colorless and transparent high-viscosity solution.

[0149] The above solution is loaded into a disposable syringe, and the metal needle is fixed on the electrospinning device. After continuous electrospinning, the entire electrospinning membrane is peeled off and heated in a vacuum oven. The electrospinning device is set to work with a rotation voltage of 15kV, a receiving distance of 15cm, a push speed of 1-10μL / min, a rotation speed of 300rpm / min, a humidity of 40%, and a temperature of 45°C. The heating temperature in the vacuum oven is 120°C for 8h. The prepared carbon fiber containing sodium-philic active metal is amorphous carbon, with a sodium-philic active metal content of 9% and a particle size range of 20-100nm for the sodium-philic metal particles.

[0150] The prepared precursor film was placed in a tubular furnace for carbonization in an argon atmosphere with a heating rate of 2°C / min, a heating temperature of 800°C, and a heating time of 4h. After cooling to room temperature, carbon fibers containing sodium-philic active metals and doped with heteroatoms were obtained.

[0151] This comparative example also provides a sodium ion battery negative electrode sheet, and the preparation method thereof is as follows:

[0152] The carbon fiber, acetylene black, and polyvinylidene fluoride prepared above containing sodium-philic active metal and doped with heteroatoms are weighed and mixed in a mass ratio of 80%:10%:10%, and N-methylpyrrolidone is added with a solid content ratio of 30%, and a mixed slurry is prepared by high-speed ball milling. The mixed slurry is coated on an aluminum foil current collector by a coating machine, vacuum dried, and rolled to obtain a negative electrode sheet for a sodium ion battery. Among them, the thickness of the aluminum foil current collector is 10 μm, and the thickness of the negative electrode active layer is 20 μm.

[0153] This comparative example also provides a sodium ion battery, and its preparation method is as follows:

[0154] The negative electrode sheet uses the above-mentioned sodium ion battery negative electrode sheet, the positive electrode sheet uses O3 layered oxide, the electrolyte uses commercial sodium battery electrolyte (manufacturer is Dongguan Kelude Experimental Equipment Technology Co., Ltd., product batch number is 20240812), and the remaining steps are assembled into a 2032 button-type sodium full battery according to conventional methods.

[0155] Comparative Example 3

[0156] This comparative example provides a sodium ion battery negative electrode sheet, and the preparation method thereof is as follows:

[0157] The acetylene black and polyvinylidene fluoride prepared above were weighed and mixed in a mass ratio of 90%:10%:10%, N-methylpyrrolidone was added, and the solid content ratio was 30%, and a mixed slurry was prepared by high-speed ball milling. The mixed slurry was coated on an aluminum foil current collector by a coating machine, vacuum dried and rolled to obtain a negative electrode sheet for a sodium ion battery. The thickness of the aluminum foil current collector was 10 μm, and the thickness of the negative electrode active layer was 20 μm.

[0158] This comparative example also provides a sodium ion battery, and its preparation method is as follows:

[0159] The negative electrode sheet uses the above-mentioned sodium ion battery negative electrode sheet, the positive electrode sheet uses P2 layered oxide, the electrolyte uses commercial sodium battery electrolyte (the manufacturer is Dongguan Kelude Experimental Equipment Technology Co., Ltd., the product batch is 20240812), and the remaining steps are assembled into a 2032 button-type sodium full battery according to conventional methods.

[0160] Comparative Example 4

[0161] This comparative example also provides a sodium ion battery, and its preparation method is as follows:

[0162] The negative electrode sheet uses commercial sodium sheet (manufactured by Dongguan Kelude Experimental Equipment Technology Co., Ltd., product batch number is 20240610), the positive electrode sheet uses O3 layered oxide, and the electrolyte uses commercial sodium battery electrolyte (manufactured by Dongguan Kelude Experimental Equipment Technology Co., Ltd., product batch number is 20240812). The remaining steps are assembled into 2032 button-type sodium full batteries according to conventional methods.

[0163] At room temperature, the sodium metal batteries prepared in Examples 1-4 and Comparative Examples 1-4 were activated at a rate of 0.1C for pre-sodiumization. The pre-sodiumized electrodes were then subjected to a cyclic charge and discharge test in a corresponding window at a rate of 0.5C until the capacity of the battery was less than 95% of the initial capacity. The number of cycles was recorded. The results are shown in Table 1:

[0164] Table 1 Electrical properties of sodium ion batteries prepared in the examples and comparative examples

[0165]

[0166] It can be seen that Examples 1-5, based on the sodium batteries assembled with carbon fibers doped with heteroatoms and containing sodium-philic active metals, show excellent cycle performance, high gram capacity and rate performance. Comparative Examples 1 to 3, prepared carbon fibers that do not contain sodium-philic active metals and do not contain heteroatoms, and the assembled sodium batteries have lower cycle performance, gram capacity and rate performance than Examples 1-5, indicating that sodium-philic active metals and doping without heteroatoms reduce polarization, avoid sodium dendrite growth, and improve conductivity. Comparative Example 4 uses a sodium battery assembled with commercial sodium sheets, which shows a drop in cycle, and has the lowest gram capacity and rate performance, indicating that carbon fibers doped with heteroatoms and containing sodium-philic active metals play a key role.

[0167] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0168] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A carbon fiber material containing sodium-philic active metal and doped with heteroatoms, characterized in that: It comprises nitrogen-doped modified carbon fibers and sodium-philic active metal particles compounded on the inner wall of the nitrogen-doped modified carbon fibers; The metal element of the sodium-philic active metal particles includes at least one of Cu, Mg, Al, Zn, Ga, Ge, Sr, Zr, Nb, Mo, Ag, In, Sn, Sb, Te, and Pb.

2. The carbon fiber material containing sodium-philic active metal and doped with heteroatoms according to claim 1, characterized in that: At least one of the following conditions is met: a. The nitrogen-doped modified carbon fiber includes at least one of nitrogen-doped modified graphitized carbon and amorphous carbon; b. The nitrogen content of the nitrogen-doped modified carbon fiber is 5-10wt%; c. The sodium-philic active metal particles are nanoparticles, and the particle size of the nanoparticles is 0.1-100 nm; d. The content of the sodium-philic active metal particles is 3-10wt%.

3. A method for preparing a carbon fiber material containing a sodium-philic active metal and doped with heteroatoms as claimed in claim 1 or 2, characterized in that: include: Mixing raw materials including a sodium-philic active metal salt, an organic reducing agent, a nitrogen-containing organic solvent, and a nitrogen-containing carbon precursor to obtain a mixed solution; Spinning the mixed solution to obtain a carbon fiber precursor; The carbon fiber precursor is carbonized and cooled to obtain the carbon fiber containing sodium-philic active metal and doped with heteroatoms.

4. The method for preparing a carbon fiber material containing sodium-philic active metal and doped with heteroatoms according to claim 3, characterized in that: At least one of the following conditions is met: d. The sodium-philic active metal salt comprises a sodium-philic active metal halide and / or a sodium-philic active metal nitrate; e. The organic reducing agent includes at least one of formaldehyde, acetaldehyde, propionaldehyde, glucose and polymethyl methacrylate; f. The nitrogen-containing organic solvent comprises at least one of N,N-dimethylformamide, N-methylcarbamates, N,N′-dimethylcarbamates, phenylcarbamates and thiocarbamates; g. The nitrogen-containing carbon precursor includes at least one of dopamine, melamine and polypyridine.

5. The method for preparing a carbon fiber material containing sodium-philic active metal and doped with heteroatoms according to claim 4, characterized in that: At least one of the following conditions is met: h. The sodium-philic active metal salt includes antimony chloride, copper chloride, magnesium chloride, aluminum chloride, zinc chloride, gallium chloride, germanium chloride, strontium chloride, zirconium chloride, niobium chloride, molybdenum chloride, silver chloride, indium chloride, tin chloride, antimony chloride, tellurium chloride, lead chloride; silver nitrate, copper nitrate, magnesium nitrate, aluminum nitrate, zinc nitrate, gallium nitrate, germanium nitrate, strontium nitrate, zirconium nitrate, niobium nitrate, molybdenum nitrate, indium nitrate, tin nitrate, antimony nitrate, tellurium nitrate, lead nitrate; i. The mass molar ratio of the sodium-philic active metal salt, the organic reducing agent, the nitrogen-containing organic solvent, and the nitrogen-containing carbon precursor is 1-10:1-10:1-10:1-10; j. When mixing the raw materials, set the stirring temperature to 50-80°C and the time to 6-12h.

6. The method for preparing a carbon fiber material containing sodium-philic active metal and doped with heteroatoms according to claim 5, characterized in that: At least one of the following conditions is met: k. The spinning is continuous electrospinning, and during the continuous electrospinning process, the rotation voltage is 10-20 kV, the receiving distance is 10-20 cm, the push speed is 1-10 μL / min, the rotation speed is 200-500 rpm / min, the humidity is 20-60%, and the temperature is 30-60 ° C; l. The carbonization process of the carbon fiber precursor is carried out in an inert gas atmosphere, wherein the inert gas includes argon or nitrogen; m. During the carbonization process of the carbon fiber precursor, the heating rate is 2-10°C / min, the heating temperature is 500-1000°C, and the heating time is 2-6h.

7. A negative electrode plate for a sodium ion battery, characterized in that: The raw materials include a negative electrode current collector and a negative electrode active layer, and the raw materials of the negative electrode active layer include the carbon fiber material containing sodium-philic active metal and doped with heteroatoms as claimed in claim 1 or 2.

8. The negative electrode plate of a sodium ion battery according to claim 7, characterized in that: The raw materials of the negative electrode active layer also include a binder and conductive carbon, and meet at least one of the following conditions: n. Taking the mass of the negative electrode active layer itself as 100%, the mass ratio of the carbon fiber doped with a sodium-philic active metal and a heteroatom, a binder, and a conductive carbon is 80-90%: 5-10%: 5-10%; o. The binder comprises at least one of styrene-butadiene rubber and polyvinylidene fluoride; p. The conductive carbon comprises one of acetylene black, conductive carbon fiber and graphene; q. The current collector comprises aluminum foil and / or copper foil; r. The thickness of the current collector is 10-20 μm; s. The thickness of the negative electrode active layer is 5-50 μm.

9. A sodium ion battery, characterized in that: Including the sodium ion battery negative electrode plate as described in claim 7 or 8.

10. An electrical equipment, characterized in that: Including the sodium ion battery as described in claim 9.

Citation Information

Cited By

  • Negative active material and preparation method thereof, negative plate and sodium ion battery

    CN120545346A